An Anatomy of Poesis : The Prose Poems of Stéphane Mallarmé - Franklin, Ursula (Book collections on Project MUSE., 2018)
A close reading, with text and translation, of each of the thirteen prose poems which Mallarme published during his life and grouped together in 1897 as the "Anecdotes ou Poemes" ofDivagations. The analysis, the first full interpretation of these poems, demonstrates that they should be considered a unified cycle, centering about the themes of the poet's creative process and his relationship to society.